CRITICAL ANALYSIS OF DENTAL TECHNOLOGY INNOVATIONS AND ASSESSING MATERIALS, TECHNIQUES, AND PATIENT OUTCOMES IN PROSTHETIC AND RESTORATIVE DENTISTRY - Jaber Ali Bani Humayyim, Mohammed Ali Bani Hamaim, Saleh Mana Hassan Alrezg, Hussain Mohsen Bin Nasser Alsallum, Salem Sager Salem Lasloom, Ali Mahdi Mana Al Saryah, Mohammed Hussain Mohammed Alofayr, Mana Hussain Hamad Alsagoor (Chelonian Research Foundation, 2023)
Regarding the recent developments in dental technology, the paper identifies innovations and their influence on prosthetic and restorative dentistry. The aspects of materials, techniques, and patient outcomes are selected for the literature review after thoroughly reviewing the subject. Research includes techniques and displays results, data, and findings through various figures, tables, and graphs. The talk gave the audience some insights into the suggested practical issues and what in the field could perform better and what could perform worse. At the end of the article, important conclusions and recommendations are presented for planning future studies and clinical practice. Keywords: Dental technology, prosthetic dentistry, restorative dentistry, materials, and techniques alike were developed and improved, and patient outcomes were influenced.